Investigation on blasted tool surfaces as a measure for material flow control in sheet-bulk metal forming - Merklein, Marion; Löffler, Maria; Gröbel, Daniel; Henneberg, Johannes (Manufacturing Review, 2019)
Highly integrated and closely tolerated functional components can be produced by sheet-bulk metal forming which is the application of bulk forming operations on sheet metal. These processes are characterized by a successive and/or simultaneous occurrence of different load conditions which reduce the geometrical accuracy of the parts. One challenge within sheet-bulk metal forming is the identification of methods to control the material flow to improve the product quality. A suitable approach is the local modification of the tribological conditions. Within this study, requirements regarding the needed adaption of the tribological system for a specific process were defined by numerical investigations. The results reveal that a local increase of the friction leads to an improved geometrical accuracy. Based on these results, abrasive blasting as a method to modify the tool surface and thus influencing the tribological behaviour was investigated. For the determination of the tribological mechanism of blasted tool surfaces, the influence of different blasting media as well as blasting pressures on the surface integrity and the friction were determined. Additionally, the functional stability of a modification was investigated. Finally, the correlations between surface properties and friction conditions were used to derive the mechanisms of blasted tool surfaces.
CRIS-Team WoS Importer:2019-06-07